Respuesta :
Question 1:
The first error occurred going from line 2 to line 3. It is wrong because 6 was multiplied by 2 while 4/4*(x-2)/3 was not.
The second error occurred going from line 5 to line 6. It is wrong because while taking -1 to the other side, it becomes +1, and -8 + 1 = -7, not -9.
Question 2:
Equations 1, 3 and 5 have the same solution 4 and equations 2 and 6 have the same solution 0.
-(7-4x)=9
4x-7=9
4x=9+7
4x=16
x=4
12 = -4(-6x-3)
12/-4 = -6x-3
-3 = -6x-3
-6x=0
x=0
5x + 34 = -2(1-7x)
5x + 34 = 14x - 2
9x - 36 = 0
9x = 36
x = 4
14 = -x + 8
x=8-14
x=-6
-8 = -x-4
x = -4 +8
x=4
x + 5 = -5x + 5
6x = 0
x = 0
Question 1:
The first error occured going from line 3 to line 4.
Why its incorrect:
instead of " ... -(2x-6) ... --> .... -2x + 6 .. .", he writes that
" ... -(2x-6) ... --> .... -2x - 6 .. .". In other words he multiplied by -1 without changing the sign.
The second error can be found going from line 5 to line 6.
Why its incorrect:
- 1 - 2x ≤ 4x - 8
- 1 - 2x + 1 ≤ 4x - 8 + 1
-2x ≤ 4x - 7
-2x -4x ≤ 4x - 4x - 7
-6x ≤ -7
Solving the inequality correctly:
5/12-(x-3)/6≤(x-2)/3
5/12-2/2*(x-3)/6≤4/4*(x-2)/3
5/12-(2x-6)/12≤(4x-8)/12
5-2x+6≤4x-8
11-2x≤4x-8
11 + 8≤ 4x + 2x
6x ≥ 19
x ≥ 19/6